A method for preparing a Zr-MOF-NH2 defluorinating agent and its application in the treatment of fluoride-containing wastewater.
By introducing the –NH2 functional group into the zirconium-based metal-organic framework, the Zr-MOF-NH2 defluorinating agent solves the problems of limited adsorption capacity and insufficient resistance to interference from coexisting ions in the treatment of fluoride-containing wastewater by existing adsorbent materials, and achieves efficient and stable deep defluorination effect.
Patent Information
- Application Number
- CN202610338363.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-03-19
- Publication Date
- 2026-06-19
Smart Images

Figure CN122234398A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of deep defluorination technology, and more specifically, to a method for preparing a Zr-MOF-NH2 defluorinating agent and its application in the treatment of fluoride-containing wastewater. Background Technology
[0002] As the global energy structure continues its transformation towards cleaner and lower-carbon energy sources, the photovoltaic industry is developing rapidly, with the manufacturing scale of photovoltaic cells and related materials constantly expanding. During photovoltaic production, a certain amount of industrial wastewater is discharged, among which fluoride-containing wastewater is characterized by large discharge volumes, high fluoride concentrations, complex compositions, and significant water quality fluctuations. Inadequate treatment can not only affect enterprises' ability to consistently meet emission standards but also pose ongoing risks to surrounding surface water, groundwater, and the ecological environment. Especially in photovoltaic manufacturing wastewater systems, in addition to fluoride ions, various inorganic salts and other coexisting ions are often present. These factors further increase mass transfer resistance and competitive adsorption effects during the defluorination process, significantly increasing the difficulty of deep defluorination treatment.
[0003] Fluorine is an essential trace element for the human body, but when the concentration of fluoride in water exceeds a reasonable range, it can adversely affect human health and the ecological environment. Long-term exposure to high concentrations of fluoride can induce dental fluorosis and skeletal fluorosis, and damage the nervous system and other tissues and organs. With increasingly stringent environmental governance requirements, various regions are tightening controls on the discharge of fluoride-containing wastewater, with some areas raising fluoride emission limits to 1.5 mg / L or even lower. Therefore, traditional treatment methods that only meet general discharge requirements are no longer adequate to meet the current practical needs for deep purification and stable compliance with discharge standards for fluoride-containing wastewater.
[0004] Currently, common technologies for treating industrial fluoride-containing wastewater include calcium salt precipitation, aluminum salt coagulation, membrane separation, ion exchange, and adsorption. While calcium salt precipitation is simple and low-cost, its limited solubility in calcium fluoride makes it difficult to further stabilize and reduce fluoride concentrations to low levels. Aluminum salt coagulation can improve removal efficiency under certain conditions, but it often requires high dosages in advanced treatment stages, leading to large sludge volumes, heavy subsequent treatment burdens, and increased risk of metal residue. Membrane separation and ion exchange offer high treatment precision, but their high equipment investment, high operating and maintenance costs, and complex membrane fouling or regeneration processes limit their widespread application in large-scale industrial wastewater treatment.
[0005] In contrast, adsorption is considered an important technical route for the deep treatment of fluoride-containing wastewater due to its relatively simple operation, strong adaptability, and ease of integration with existing treatment processes. However, existing adsorption materials still suffer from limitations in practical applications, including limited adsorption capacity, sensitivity to pH changes, insufficient resistance to interference from coexisting ions, and unsatisfactory regeneration performance. This is particularly true in complex water conditions such as photovoltaic wastewater, where achieving high-efficiency removal, stable operation, and economic feasibility is often difficult. In recent years, metal-organic frameworks (MOFs) have shown good application potential in wastewater treatment due to their large specific surface area, tunable pore structure, and ease of functionalization. However, existing MOF materials still face challenges in deep fluoride ion removal, including insufficient utilization of active sites, less than ideal selectivity, and the need to improve their adaptability to specific wastewater conditions.
[0006] Therefore, there is an urgent need in this field for a defluorination material and its application method that can achieve efficient removal of fluoride ions from fluoride-containing wastewater under a wide range of application conditions, has high adsorption capacity and good selectivity, and at the same time takes into account the simplicity of preparation process and the feasibility of practical application. Summary of the Invention
[0007] To overcome the aforementioned deficiencies in the prior art, this invention provides a method for preparing a Zr-MOF-NH2 defluorinating agent and its application in the treatment of fluoride-containing wastewater. By synergistically introducing 1,3,5-pyromellitic acid and 5-aminoisophthalic acid into a zirconium-based metal-organic framework, a Zr-MOF-NH2 defluorinating agent with a –NH2 functional group is prepared and used for the advanced treatment of fluoride-containing wastewater, thereby solving the problems mentioned in the background art.
[0008] To achieve the above objectives, the present invention provides the following technical solution:
[0009] A method for preparing a Zr-MOF-NH2 defluorinating agent includes the following steps: Step 1: Add 1,3,5-pyromellitic acid, 5-aminoisophthalic acid, and concentrated hydrochloric acid to a mixed solution of acetic acid and water, and stir until homogeneous to obtain a precursor solution; Step 2: Add ZrOCl2·8H2O to the precursor solution, mix thoroughly, and then stir and reflux under heating conditions. After the reaction is completed, cool to room temperature and centrifuge to obtain a solid crude product; Step 3: Soak the solid crude product in an organic solvent and stir, then centrifuge to obtain a solid product. Repeat the soaking, stirring, and separation process three times; Step 4: Dry the obtained product in a vacuum drying oven to obtain a white powdery Zr-MOF-NH2 defluorinating agent; wherein, the obtained Zr-MOF-NH2 defluorinating agent is used for the treatment of fluoride-containing wastewater.
[0010] As a further embodiment of the present invention, in step one, the molar ratio of 1,3,5-pyromellitic acid to 5-aminoisophthalic acid is 5:1 to 1:1, preferably 3:1, the volume ratio of acetic acid to water is 1:1, and the volume ratio of concentrated hydrochloric acid to acetic acid is 1:80 to 1:120, preferably 1:100.
[0011] As a further embodiment of the present invention, the molar ratio of ZrOCl2·8H2O to 5-aminoisophthalic acid in step two is 18:1 to 6:1, preferably 12:1.
[0012] As a further embodiment of the present invention, the reaction temperature in step two is 90℃-120℃, preferably 110℃; the reaction time is 12-24h, preferably 18h.
[0013] As a further embodiment of the present invention, the organic solvent in step three is ethanol or acetone, preferably ethanol; the stirring time is 20-60 min, preferably 30 min.
[0014] As a further embodiment of the present invention, the drying temperature in step four is 60-100℃, and the drying time is 5-10h.
[0015] As a further aspect of the present invention, the Zr-MOF-NH2 defluorinating agent is a zirconium-based metal-organic framework material with –NH2 functional groups.
[0016] This invention discloses a method for preparing a Zr-MOF-NH2 defluorinating agent and its technical effects and advantages in the treatment of fluoride-containing wastewater:
[0017] This invention introduces 1,3,5-pyromellitic acid and 5-aminoisophthalic acid synergistically into a zirconium-based metal-organic framework system to prepare a Zr-MOF-NH2 defluorinating agent with a –NH2 functional group. This material has both zirconium-based active sites and amino functional sites, which have a stronger affinity for fluoride ions and can effectively improve adsorption capacity and defluorination efficiency. From the perspective of material structure design, it improves its applicability for the deep treatment of fluoride-containing wastewater.
[0018] The Zr-MOF-NH2 defluorinating agent prepared in this invention exhibits excellent static defluorination performance. When the dosage is 0.5 g / L, for simulated fluoride-containing wastewater with an initial concentration of 10.68 mg / L, the fluoride ion removal rate remains above 90% within the pH range of 3 to 7, and the fluoride ion concentration after adsorption is below 1.0 mg / L. When the adsorbent dosage is 0.2 g / L and the initial concentration is 19.38 mg / L, the adsorption capacity reaches 60.80 mg / g under pH=3 conditions, demonstrating a high deep defluorination capability.
[0019] The Zr-MOF-NH2 defluorinating agent prepared in this invention exhibits good adaptability and anti-interference ability to actual fluoride-containing wastewater. Verification was conducted using actual wastewater from a photovoltaic enterprise. Under conditions of pH=6, initial fluoride ion concentration of 12.84 mg / L, and dosage of 0.7 g / L, the fluoride ion concentration in the treated wastewater could be reduced to 0.486 mg / L, achieving a removal rate of 96.21%. This meets the requirements for advanced treatment of fluoride-containing wastewater, indicating that the material is suitable not only for simulated systems but also for complex actual water bodies.
[0020] The preparation method of this invention is simple and mild, using an acetic acid / water system to complete the precursor construction and zirconium-based metal-organic framework synthesis. The target product can be obtained by washing with organic solvent and vacuum drying. It has good operability and scale-up application prospects. At the same time, dynamic adsorption experiments show that the defluorinating agent has a large breakthrough volume under the conditions of a flow rate of 10 BV / h and an initial fluoride ion concentration of 10.12 mg / L, indicating that it has good continuous operation performance and is suitable for engineering applications. Attached Figure Description
[0021] Figure 1 This is a graph showing the change in the adsorption capacity of the Zr-MOF-NH2 adsorbent for fluoride ions under different pH conditions according to the present invention.
[0022] Figure 2 This is a dynamic adsorption breakthrough curve of the Zr-MOF-NH2 adsorbent for fluoride-containing wastewater according to the present invention. Detailed Implementation
[0023] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0024] Example 1
[0025] In this embodiment, 0.945 g (4.5 mmol) of 1,3,5-pyromellitic acid, 0.272 g (1.5 mmol) of 5-aminoisophthalic acid, 60 mL of acetic acid, 60 mL of H₂O, and 600 μL of concentrated hydrochloric acid were added sequentially to a 500 mL round-bottom flask. The mixture was magnetically stirred for 10 min at room temperature to ensure thorough mixing of the components, yielding a precursor solution. At this point, the molar ratio of 1,3,5-pyromellitic acid to 5-aminoisophthalic acid was 3:1, the volume ratio of acetic acid to H₂O was 1:1, and the volume ratio of concentrated hydrochloric acid to acetic acid was 1:100.
[0026] Subsequently, 5.796 g (18.0 mmol) of ZrOCl2·8H2O was added to the precursor solution, and magnetic stirring was continued for 10 min to ensure uniform dispersion of the zirconium source in the system and sufficient contact with the two organic ligands. At this point, the molar ratio of ZrOCl2·8H2O to 5-aminoisophthalic acid was 12:1. After thorough mixing, the reaction system was refluxed and stirred in an oil bath at 110 °C for 18 h. After the reaction was completed, the system was naturally cooled to room temperature, and centrifugation yielded a white powdery crude product.
[0027] The crude product was soaked in ethanol and stirred continuously at room temperature for 30 minutes before centrifugation. The supernatant was discarded, and the soaking, stirring, and centrifugation process was repeated three times with fresh ethanol to remove unreacted raw materials, free small molecules, and residual impurities. The washed solid sample was dried in a vacuum drying oven at 80℃ for 8 hours to obtain a white powdery Zr-MOF-NH2 defluorinating agent. The Zr-MOF-NH2 defluorinating agent obtained through the above steps is a zirconium-based metal-organic framework material with –NH2 functional groups. 1,3,5-pyromellitic acid participates in the construction of the main framework of the zirconium-based metal-organic framework, while 5-aminoisophthalic acid introduces –NH2 functional groups into the material while participating in coordination construction.
[0028] In this embodiment, the Zr-MOF-NH2 defluorinating agent described above was used in a static adsorption experiment. The simulated fluoride-containing wastewater was prepared using sodium fluoride and ultrapure water, while the actual fluoride-containing wastewater was wastewater from a photovoltaic enterprise. The initial pH of the wastewater was adjusted using sulfuric acid or sodium hydroxide. A certain amount of Zr-MOF-NH2 defluorinating agent was weighed and added to 100 mL of fluoride-containing wastewater. The sample was placed in a 25°C constant-temperature shaker and shaken at 200 rpm for 1 hour. After the reaction, the adsorbent was separated using a water-based filter. The filtrate contained... The concentration was determined using the fluoride ion-selective electrode method. The static adsorption results of this embodiment are shown in Table 1.
[0029] Table 1 Static fluoride removal results of Zr-MOF-NH2 adsorbent on fluoride-containing wastewater
[0030] Fluoride-containing wastewater pH Dosage (g / L) F⁻ concentration before adsorption (mg / L) F⁻ concentration after adsorption (mg / L) Adsorption efficiency (%) Simulated wastewater 3 0.5 10.68 0.213 98.01 Simulated wastewater 4 0.5 10.68 0.412 96.14 Simulated wastewater 5 0.5 10.68 0.537 94.97 Simulated wastewater 6 0.5 10.68 0.928 91.31 Simulated wastewater 7 0.5 10.68 0.998 90.66 Simulated wastewater 3 0.2 19.38 7.22 62.75 Simulated wastewater 4 0.2 19.38 8.113 58.14 Simulated wastewater 5 0.2 19.38 9.519 50.88 Simulated wastewater 6 0.2 19.38 10.45 46.08 Simulated wastewater 7 0.2 19.38 12.27 36.69 Actual wastewater 6 0.7 12.84 0.486 96.21
[0031] As shown in Table 1, when the simulated wastewater initially... At a concentration of 10.68 mg / L and an adsorbent dosage of 0.5 g / L, under pH conditions of 3, 4, 5, 6, and 7, the adsorption... The concentrations were 0.213 mg / L, 0.412 mg / L, 0.537 mg / L, 0.928 mg / L, and 0.998 mg / L, all below 1.0 mg / L; the corresponding removal rates were 98.01%, 96.14%, 94.97%, 91.31%, and 90.66%, all above 90%, indicating that the Zr-MOF-NH2 defluorinating agent prepared in this embodiment has good deep defluorination capability in the pH range of 3 to 7.
[0032] Table 1 also shows that, under actual photovoltaic wastewater conditions, when the pH is 6 and the initial... When the concentration is 12.84 mg / L and the adsorbent dosage is 0.7 g / L, the treated... The concentration dropped to 0.486 mg / L, and the removal rate was 96.21%, indicating that the material obtained in this embodiment still has a high defluoridation efficiency in real wastewater systems with more complex compositions, and can meet the requirements of deep treatment.
[0033] Example 2
[0034] In this embodiment, 1.008 g (4.8 mmol) of 1,3,5-pyromellitic acid, 0.218 g (1.2 mmol) of 5-aminoisophthalic acid, 60 mL of acetic acid, 60 mL of H₂O, and 600 μL of concentrated hydrochloric acid were added sequentially to a 500 mL round-bottom flask. The mixture was magnetically stirred for 10 min at room temperature to ensure thorough mixing and obtain the precursor solution. At this point, the molar ratio of 1,3,5-pyromellitic acid to 5-aminoisophthalic acid was 4:1, the volume ratio of acetic acid to H₂O was 1:1, and the volume ratio of concentrated hydrochloric acid to acetic acid was 1:100.
[0035] 5.796 g (18.0 mmol) of ZrOCl2·8H2O was added to the above precursor solution, and the mixture was magnetically stirred for 10 min to ensure homogeneous mixing of the zirconium source and ligand. The reaction solution was then refluxed in an oil bath at 110 °C for 18 h. After the reaction, the mixture was allowed to cool naturally to room temperature and centrifuged to obtain a white powdery crude product. The crude product was then immersed in acetone and stirred continuously at room temperature for 60 min before centrifugation. The supernatant was discarded, and the process of immersion, stirring, and centrifugation was repeated three times with fresh acetone. The washed sample was then dried in a vacuum drying oven at 60 °C for 10 h to obtain a white powdery Zr-MOF-NH2 defluorinating agent.
[0036] In this embodiment, the soaking and washing solvent was changed from ethanol to acetone, and the drying conditions were changed from 80℃ and 8h to 60℃ and 10h. The resulting sample was still a white powdery Zr-MOF-NH2 defluorinating agent, indicating that the preparation method has certain process adaptability in terms of soaking and washing solvent and drying conditions. This result further shows that when the dual ligands, zirconium source, mixed solvent, and reflux reaction conditions are kept within a certain range, different post-treatment combinations can also stably obtain the target defluorinating material.
[0037] The Zr-MOF-NH2 defluorinating agent obtained in this embodiment was subjected to a defluorination experiment using the static adsorption method described in Example 1. The results showed that the material can also be used for the treatment of fluoride-containing wastewater.
[0038] Example 3
[0039] Under the same static adsorption conditions as in Example 1, the adsorption capacity of the Zr-MOF-NH2 fluoride remover under different pH conditions was further calculated to evaluate its effectiveness. Adsorption performance.
[0040] In the adsorption capacity experiment, the simulated fluoride-containing wastewater was prepared using sodium fluoride and ultrapure water. The concentration was 19.38 mg / L, the adsorbent dosage was 0.2 g / L, and the pH of the wastewater was adjusted to 3, 4, 5, 6, and 7 using sulfuric acid or sodium hydroxide. The corresponding mass of Zr-MOF-NH2 defluorinating agent was added to 100 mL of the wastewater to be treated. The mixture was shaken at 200 rpm for 1 hour at 25℃ in a constant temperature shaker. After filtration, the F⁻ concentration in the filtrate was measured, and the adsorption capacity was calculated using the adsorption capacity formula. , =( )V / m, where, Before adsorption Concentration, in mg / L; For adsorption Concentration, in mg / L; V, wastewater volume, in L; m, adsorbent mass, in g. The adsorption capacity results of this example are shown in Table 2.
[0041] Table 2 Adsorption capacity results of Zr-MOF-NH2 adsorbent under different pH conditions
[0042] pH Adsorbent dosage (g / L) F⁻ concentration before adsorption (mg / L) F⁻ concentration after adsorption (mg / L) Adsorption efficiency (%) <![CDATA[Adsorption capacity q t (mg / g)]]> 3 0.2 19.38 7.22 62.75 60.80 4 0.2 19.38 8.113 58.14 56.34 5 0.2 19.38 9.519 50.88 49.31 6 0.2 19.38 10.45 46.08 44.65 7 0.2 19.38 12.27 36.69 35.55
[0043] Table 2 shows that under pH conditions of 3, 4, 5, 6, and 7, the adsorption... The concentrations were 7.22 mg / L, 8.113 mg / L, 9.519 mg / L, 10.45 mg / L, and 12.27 mg / L, respectively; corresponding adsorption capacities The adsorption capacities were 60.80 mg / g, 56.34 mg / g, 49.31 mg / g, 44.65 mg / g, and 35.55 mg / g, respectively. The adsorption capacity gradually decreased with increasing pH, indicating that acidic conditions are more conducive to the material's adsorption capacity. The adsorption effect. The trend of adsorption capacity change is as follows: Figure 1 As shown in the figure, the curve gradually decreases from about 60 mg / g at pH 3 to about 35 mg / g at pH 7, which is consistent with the data change in Table 2.
[0044] In the dynamic adsorption experiment, the simulated fluoride-containing wastewater was prepared using sodium fluoride and ultrapure water. The concentration was 10.12 mg / L, and the pH was adjusted to 6 using sulfuric acid or sodium hydroxide. A continuous flow experiment was conducted using a glass adsorption column with an inner diameter of 15 mm, a length of 300 mm, and an insulating jacket. 7 mL of Zr-MOF-NH2 defluorinating agent (8.2513 g) was packed into the column. The experiment was conducted using a bottom-feed method, with the flow rate controlled at 10 BV / h (1.17 mL / min) using a medium-flow digital transfer peristaltic pump. 35 mL of effluent was collected each time, and the concentration of fluoride in the effluent was determined using a fluoride ion selective electrode method. The concentration was determined, with 1.5 mg / L as the breakthrough point. The dynamic adsorption results of this example are shown in Table 3.
[0045] Table 3. Results of dynamic adsorption experiments on Zr-MOF-NH2 adsorbent
[0046] Processing volume (BV) F⁻ concentration in effluent (mg / L) 0 0.10 200 0.11 400 0.13 600 0.18 800 0.21 1000 0.24 1200 0.35 1400 0.45 1600 0.65 1800 0.90 2000 1.05 2100 1.28 2180 1.523
[0047] Table 3 shows that in the initial stage of dynamic adsorption, the effluent... The concentration remained at a low level, generally below 0.25 mg / L in the range of 0–1000 BV; as the treatment volume increased, the effluent... The concentration increases slowly; when the treatment volume reaches 1600 BV, the rate of concentration increase accelerates significantly; when the treatment volume reaches 2180 BV, the effluent... The concentration was 1.523 mg / L, reaching the breakthrough point. Its trend is as follows: Figure 2 As shown in the figure, the curve is relatively flat at the beginning and gradually rises at the end, which corresponds to the data in Table 3. This result indicates that the Zr-MOF-NH2 defluorinating agent obtained in this embodiment has a long effective operating cycle and high dynamic treatment capacity under continuous flow conditions, and can be applied to the continuous deep treatment of fluoride-containing wastewater.
[0048] Example 4
[0049] This embodiment describes the application process of Zr-MOF-NH2 defluorinating agent in the advanced treatment of photovoltaic fluoride-containing wastewater, further verifying the applicability and treatment effect of this material under real industrial wastewater conditions. The Zr-MOF-NH2 defluorinating agent used in this embodiment was prepared using the method of Example 1. Specifically, in a mixed system of acetic acid and H2O, using 1,3,5-pyromellitic acid and 5-aminoisophthalic acid as organic ligands, and ZrOCl2·8H2O as the zirconium source, a white powder product was obtained after reflux reaction, centrifugation, organic solvent soaking and washing, and vacuum drying under acidic conditions. The obtained material is a zirconium-based metal-organic framework defluorinating agent with –NH2 functional groups, which can be directly used for the treatment of fluoride-containing wastewater.
[0050] The wastewater treated in this embodiment was taken from the production wastewater of a photovoltaic enterprise. This type of wastewater originates from the drainage of related processes in photovoltaic manufacturing and is characterized by relatively high fluoride ion concentration, complex background components, and significant water quality fluctuations, making it closer to actual industrial application conditions than simulated wastewater. To ensure stable subsequent treatment conditions, the wastewater sample was homogenized and mixed before adsorption treatment to maintain overall water quality uniformity. Then, its initial... Concentration and pH. The initial concentration of the actual photovoltaic wastewater was measured. The concentration was 12.84 mg / L. Considering that the material of this invention has good defluorination capacity under acidic to near-neutral conditions, and taking into account the convenience of adjusting operating conditions in practical applications, this embodiment adjusts the pH of the wastewater to 6 before adsorption treatment. Sulfuric acid or sodium hydroxide is used for micro-adjustment during pH adjustment, and the system is thoroughly stirred after each adjustment to ensure pH stability before proceeding to the next adsorption experiment.
[0051] In the intermittent treatment process of actual wastewater, 100 mL of actual photovoltaic wastewater, after pH adjustment, was placed in a reaction vessel, and then Zr-MOF-NH2 defluorinating agent was added at a dosage of 0.7 g / L. To ensure the adsorbent reacts with the actual wastewater... To ensure sufficient contact, in this embodiment, the sample was placed in a constant-temperature shaker at 25°C and shaken at 200 rpm for 1 hour. The treatment temperature was controlled at 25°C to accurately reflect the material's performance under normal conditions; the shaking rate was controlled at 200 rpm to reduce liquid film diffusion resistance and improve mass transfer efficiency between the adsorbent and wastewater; the contact time was set to 1 hour to ensure treatment efficiency while also meeting the processing cycle requirements in practical applications. After the above adsorption process, an aqueous filter was used to separate the adsorbent from the treated wastewater. The filtrate was collected, and the concentration of fluoride ions in the filtrate was determined using a fluoride ion-selective electrode method. concentration.
[0052] To make the actual application conditions and processing results of this embodiment clearer, the relevant operating parameters and test results are listed in Table 4.
[0053] Table 4. Application conditions and results of Zr-MOF-NH2 defluorinating agent in actual photovoltaic fluoride-containing wastewater treatment.
[0054] Wastewater type initial pH Adsorbent dosage (g / L) Wastewater volume (mL) Processing temperature (°C) Oscillation rate (rpm) Processing time (h) F⁻ concentration before treatment (mg / L) F⁻ concentration after treatment (mg / L) Removal rate (%) Photovoltaic wastewater 6 0.7 100 25 200 1 12.84 0.486 96.21
[0055] Table 4 shows that under the conditions of pH 6, adsorbent dosage of 0.7 g / L, wastewater volume of 100 mL, treatment temperature of 25℃, oscillation rate of 200 rpm, and treatment time of 1 h, the actual photovoltaic wastewater contains... The concentration decreased from 12.84 mg / L to 0.486 mg / L, achieving a removal rate of 96.21%. This result demonstrates that the Zr-MOF-NH2 defluorinating agent described in this invention not only achieves high removal efficiency in simulated wastewater systems but also exhibits significant deep defluorination capabilities in real photovoltaic wastewater with more complex compositions, especially after treatment. The concentration dropping below 1.0 mg / L indicates that the material has a relatively stable effect in actual water bodies and can meet the requirements of advanced treatment under high standards.
[0056] From a practical application perspective, the reason why the Zr-MOF-NH2 defluorinating agent in this embodiment can maintain a high defluorination efficiency in complex wastewater systems is related to the material's structure and activity characteristics. This material provides defluorination efficiency through its zirconium-based metal-organic framework structure. The adsorption sites are located at the site, and the introduction of the –NH2 functional group enhances the adsorption capacity. The material's ability to remove fluoride allows it to maintain good removal efficiency even in the presence of multiple coexisting components in actual wastewater. Compared to materials that rely solely on general physical adsorption, the material of this invention is more effective in reducing effluent quality when treating real industrial fluoride-containing wastewater. Concentration, and increase the likelihood of final treatment meeting standards.
[0057] In practical applications, in addition to the treatment effect of a single batch, the continuity of the treatment process and the operational seamlessness also need to be considered. Based on the application method of this embodiment, for wastewater samples with small treatment volumes or those used for rapid on-site evaluation, the above-mentioned intermittent adsorption treatment method can be adopted. That is, the pH of the actual wastewater is first adjusted, and then Zr-MOF-NH2 defluorinating agent is added according to the set dosage. After isothermal oscillation adsorption, solid-liquid separation is completed and the fluoride in the water is detected. Concentration. This method is simple to operate and facilitates quick determination of whether a batch of actual wastewater can achieve deep defluoridation using the material of this invention. It is also beneficial for assessing the raw water concentration. Adjust the dosage or contact time promptly if the concentration changes.
[0058] For treatment scenarios requiring long-term continuous operation, Zr-MOF-NH2 defluorinating agent can be packed into an adsorption column to implement continuous flow treatment, based on the results of intermittent treatment. In continuous flow applications, the operating mode used in the aforementioned dynamic adsorption experiment can be referenced, controlling the bed packing volume, influent flow rate, and effluent flow rate. The operating status of the adsorbent is determined by changes in concentration. In actual operation, the pre-adjusted fluoride-containing wastewater can be continuously introduced into an adsorption column filled with Zr-MOF-NH2 defluorinating agent, and the concentration of the wastewater can be detected at regular intervals. Concentration. When effluent... When the concentration is maintained within the target control range, it indicates that the adsorbent is operating effectively; when the concentration in the effluent... When the concentration gradually increases and approaches the set control value, it indicates that the adsorption sites of the material are gradually approaching saturation, requiring subsequent treatment or replacement. This application logic is consistent with the relatively long effective operating cycle exhibited by the material of this invention under dynamic conditions, and also indicates that it is not only suitable for small-scale experiments under laboratory conditions, but also has the application basis for transitioning to continuous processing technology.
[0059] Regarding the subsequent use of materials, the application method of this invention also considers the recycling of the adsorbent. When the adsorption capacity of the Zr-MOF-NH2 defluorinating agent decreases after multiple uses or approaches the breakthrough state during continuous operation, the water intake can be stopped, and the adsorbent material can be removed from the treatment system for subsequent regeneration. According to the application scheme of this invention, the Zr-MOF-NH2 defluorinating agent after adsorption saturation can be regenerated through elution, drying, etc., and the regenerated material can continue to be used for the treatment of fluoride-containing wastewater. This process helps to improve the utilization efficiency of the adsorbent, reduce material consumption, and thus reduce the operating cost in the actual wastewater treatment process. Since the material used in this invention itself belongs to the zirconium-based metal-organic framework structure and the preparation process is relatively simple, the application method of regeneration and reuse is more conducive to reflecting its comprehensive value in industrial scenarios.
[0060] This embodiment also illustrates the complete application chain of the present invention in actual wastewater treatment, from influent control to effluent evaluation. Specifically, actual photovoltaic wastewater is first sampled and homogenized, and then the raw water quality is measured. The concentration and pH were adjusted to bring the wastewater into a suitable operating range for adsorption treatment. Then, Zr-MOF-NH2 defluorinating agent was added at the set dosage, and the adsorption process was completed under constant temperature and vibration conditions. After adsorption, solid-liquid separation was achieved through filtration, and the fluoride ion-selective electrode method was used to detect the fluoride ions in the water. The concentration was then used to evaluate the treatment effect of the material of this invention on actual photovoltaic wastewater. The process chain is clearly defined and the steps are straightforward, reflecting both the application of the material of this invention in actual wastewater and providing a referable implementation path for subsequent scale-up applications.
[0061] In summary, this embodiment demonstrates that the Zr-MOF-NH2 defluorinating agent provided by this invention can be directly applied to the advanced treatment of actual photovoltaic wastewater containing fluoride. Under the conditions described in this embodiment, the actual wastewater contains... The concentration could be reduced from 12.84 mg / L to 0.486 mg / L, with a removal rate of 96.21%, indicating that the material still has high defluorination efficiency and good application adaptability in real industrial wastewater systems. Furthermore, the material of this invention can be used in both intermittent adsorption treatment and continuous flow adsorption processes, and can be regenerated after adsorption saturation through elution and drying for continued use. Therefore, it has good application prospects in the deep treatment of fluoride-containing wastewater, especially photovoltaic fluoride-containing wastewater.
[0062] The above description is merely a specific embodiment of this application, but the scope of protection of this application is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in this application should be included within the scope of protection of this application. Therefore, the scope of protection of this application should be determined by the scope of the claims.
[0063] In conclusion, the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for preparing a Zr-MOF-NH2 defluorinating agent, characterized in that, The process includes the following steps: Step 1: Add 1,3,5-pyromellitic acid, 5-aminoisophthalic acid, and concentrated hydrochloric acid to a mixed solution of acetic acid and water, stir until homogeneous, and obtain a precursor solution; Step 2: Add ZrOCl2·8H2O to the precursor solution, mix thoroughly, and then stir and reflux under heating conditions. After the reaction is complete, cool to room temperature and centrifuge to obtain a solid crude product; Step 3: Soak the solid crude product in an organic solvent and stir, then centrifuge to obtain a solid product. Repeat the soaking, stirring, and separation process three times; Step 4: Dry the obtained product in a vacuum drying oven to obtain a white powdery Zr-MOF-NH2 defluorinating agent; wherein, the obtained Zr-MOF-NH2 defluorinating agent is used for the treatment of fluoride-containing wastewater.
2. The preparation method of a Zr-MOF-NH2 defluorinating agent according to claim 1, characterized in that, In step one, the molar ratio of 1,3,5-pyromellitic acid to 5-aminoisophthalic acid is 5:1 to 1:1, preferably 3:1; the volume ratio of acetic acid to water is 1:1; and the volume ratio of concentrated hydrochloric acid to acetic acid is 1:80 to 1:120, preferably 1:
100.
3. The method for preparing a Zr-MOF-NH2 defluorinating agent according to claim 1, characterized in that, In step two, the molar ratio of ZrOCl2·8H2O to 5-aminoisophthalic acid is 18:1 to 6:1, preferably 12:
1.
4. The preparation method of a Zr-MOF-NH2 defluorinating agent according to claim 1, characterized in that, The reaction temperature in step two is 90℃-120℃, preferably 110℃; the reaction time is 12-24h, preferably 18h.
5. The method for preparing a Zr-MOF-NH2 defluorinating agent according to claim 1, characterized in that, In step three, the organic solvent is ethanol or acetone, preferably ethanol; the stirring time is 20-60 min, preferably 30 min.
6. The method for preparing a Zr-MOF-NH2 defluorinating agent according to claim 1, characterized in that, The drying temperature in step four is 60–100°C, and the drying time is 5–10 hours.
7. The method for preparing a Zr-MOF-NH2 defluorinating agent according to claim 1, characterized in that, The Zr-MOF-NH2 defluorinating agent is a zirconium-based metal-organic framework material with –NH2 functional groups.
